Cultural experience of the young generation in Polish families in the Vilnius cultural borderland - Szerląg, Alicja (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2018)
The aim of this study was to define the specificity of the cultural experiences of the young generation of Poles in the Vilnius cultural borderland, in particular regarding their cultural identifications in family environment. The research exploration, concerning the above outlined issues, was carried out with the application of the method of diagnostic survey. The research embraced 106 teenagers coming from Polish families, and living in the Vilnius region. Relying on the conclusions from own research, carried out amongst the young generation of Poles living in the Vilnius area, a conceptualisation of the cultural space of the family in a borderland took place, followed by the distinction of its primary dimensions, i.e. the extant, succeeded and accomplished. With reference to each of the latter the author described generating factors that are of key importance in the process of the cultural identification of the young generation functioning in the cultural borderland. On such grounds the conclusions tackled not only the cultural orientations of the researched, but equally their cultural capital with regards to the process of establishing a community in the multicultural environment. For the latter, the culture of the borderland proves to function as a point of reference, entailing cross-cultural and cross-national features.
Keywords: family home; identity; cultural space of the family; dimensions of the cultural identification